WRIST WEIGHTS FOR FITNESS OF BADMINTON PLAYERS - P. Nufable, Belenda (President University, 2024)
This descriptive-experimental study sought to determine the effectiveness of wrist weights on the thirty (30) purposely chosen respondents from the WVSU Pototan Campus in terms of muscular strength, flexibility, muscular endurance, and power. In addition, the accuracy of shuttle cock landing for both high and low serves across the court was investigated. To ascertain whether there was a significant difference in the participant’s level of fitness before and after using wrist weights and the accuracy of shuttle cock landing in cross-court for both high and low serve. Quasai-experemental method was employed, the data were gathered, and analyzed using the mean, standard deviation, frequency, and t-test. High muscular strength, with low flexibility were found in the study, however, muscular endurance and power got very high results. Both high and low serve exhibited very effective accuracy for shuttle cock landings. The level of fitness of the articiants showed significant differences in terms of muscular strength, flexibility, muscular endurance, and power. Similarly, the accuracy of shuttle cock landing for both high and low serve showed a noticeable difference. It was suggested that additional research be done in this direction utilizing different parameters and variables to verify the accuracy of the study’s findings.